"Click"‐Like η6‐Metalation/Demetalation of Aryl Iodides as a Means of Turning "ON/OFF" Halogen Bond Donor Functionality. Issue 13 (9th February 2022) - Kelly, Andrew W.; Holman, K. Travis
Abstract: η 6 ‐Metalated aryl halides are recognized as a class of halogen bond (XB) donors. Click‐like η 6 ‐metalation/demetalation of aryl iodides by cyclopentadienylruthenium(II) ([CpRu II ] + ) is shown to turn ON/OFF (amplify/suppress) XB donor functionality. [CpRu(MeCN)3 ][PF6 ] is shown to react quantitatively with iodobenzenes (ArI n, n =1, 2) to yield [CpRu(η 6 ‐ArI n )][PF6 ] compounds. Photochemical demetalation (405 nm) quantitatively reverts these compounds to ArI n and [CpRu(MeCN)3 ][PF6 ]. Crystal structures of [CpRu(ArX n )] + salts show that the [CpRu(ArI n )] + cations are strong, charge‐assisted XB donors analogous to iodopyridinium cations. XB‐induced association of [CpRu(C6 H5 I)] + with diazobicyclo[2.2.2]octane (DABCO) is established by NMR spectroscopy. [CpRu(C6 H5 I)][BPh4 ] and [CpRu(1, 4‐C6 H4 I2 )][BPh4 ] co‐crystallize with DABCO and the structure of [CpRu(1, 4‐C6 H4 I2 )][BPh4 ]⋅DABCO⋅Et2 O is reported. DFT calculations support amplification of the XBing capabilities of aryl iodides upon [CpRu] + ‐metalation. Abstract : Click On! η 6 ‐Coordination of cationic cyclopentadienylruthenium(II) moieties is demonstrated to be a convenient, quantitative method for the click‐like activation of aryl iodides as halogen bond donors. Photochemical demetalation using violet LEDs in MeCN returns the metal to its starting material form and supresses halogen bonding functionality. The cycle provides a reversible "ON/OFF" switch for controlling the halogen bond donor strength of aryl iodides.